American cinema. - Klarer, Alain; Foster, Elizabeth; Robertson, Cliff, 1923-2011 (Academic Video Online, 1995)
Television first arrived in American homes just as the Hollywood studio system was collapsing. As the new medium took hold, so did a new era of motion picture entertainment. Top directors, actors, and film scholars trace the influence of each medium on the other, from the live and fresh dramas of the Golden Age of Television and the growth of Hollywood spectacles to the megalithic entertainment industry of today. About the Series: A video instructional series on film history for college and high school classrooms and adult learners; 10 one-hour and 3 half-hour video programs and coordinated books. Using clips from more than 300 of the greatest movies ever made, this series explores film history and American culture through the eyes of over 150 Hollywood insiders, including Clint Eastwood, Steven Spielberg, and Michael Eisner. In-depth treatments present film as a powerful economic force, potent twentieth-century art form, and viable career option. American Cinema connects subjects such as history, business, and English with other studies. In addition, it is a perfect vehicle for developing visual and media literacy skills and can be used as a springboard for creative-writing endeavors and media production. Produced by the New York Center for Visual History in association with KCET/Los Angeles and the BBC. 1995.